Anthropomorphized Helpers Undermine Autonomy and Enjoyment in Computer Games - Kim, Sara; Chen, Rocky Peng; Zhang, Ke (Journal of Consumer Research, 2016)
Abstract Although digital assistants with humanlike features have become prevalent in computer games, few marketing studies have demonstrated the psychological mechanisms underlying consumers’ reactions to digital assistants and their subsequent influence on consumers’ game enjoyment. To fill this gap, the current study examined the effect of anthropomorphic representations of computerized helpers in computer games on game enjoyment. In the current research, consumers enjoyed a computer game less when they received assistance from a computerized helper imbued with humanlike features than from a helper construed as a mindless entity. We offer a novel mechanism that the presence of an anthropomorphized helper can undermine individuals’ perceived autonomy during a computer game. Across six experiments, we show that the presence of an anthropomorphized helper reduced game enjoyment across three different games. By measuring participants’ perceived autonomy (study 1) and employing moderators such as importance of autonomy (studies 2, 3, and 4), we also provide evidence that the reduced feeling of autonomy serves as the mechanism underlying the backfiring effect. Finally, we demonstrate that the effect of anthropomorphism on game enjoyment can be extended to other game-related outcomes, such as individuals’ motivation to persist in the game (studies 4 and 5).